Luminescent Au6 and Au8 nanoclusters from ligand induced etching of Au nanoparticles. (11th December 2019) - Bain, Dipankar; Maity, Subarna; Debnath, Tanay; Das, Abhijit Kumar; Patra, Amitava
Abstract: Metal nanoclusters (NCs) with atomic precision are receiving significant attention because of their widespread applications in the field of energy-related materials, sensing and biomedicine. In this work, luminescent Au nanoclusters (NCs) are synthesized from Au nanoparticles (NPs) by core-etching process in presence of excess glutathione (GSH) ligand. Electrospray ionization (ESI) mass spectrometric study suggests the formation of polydisperse Au6 and Au8 NCs at elevated temperature (70 °C). The HOMO-LUMO band gap of Au6 and Au8 clusters are calculated from optimized structure. The photoluminescence maximum of as-prepared Au NCs is observed at 421 nm after excitation at 340 nm with 4.20% quantum yield (QY). Lifetime of the NCs is found to be 0.57 ns in excited state, which arises because of electronic transitions from low-lying d-bands to excited state sp bands of core-state only. Moreover the luminescence intensity of as-prepared Au NCs is found to be very stable both in acidic and basic medium. The synthesis of luminescent Au NCs from non-luminescent plasmonic Au NPs is beneficial for various applications such as sensing, biomedicine, and light emitting devices.